ARTIFICIAL INTELLIGENCE AND DIGITAL PLATFORMS AS A DRIVER OF EDUCATIONAL TRANSFORMATION (Eureka Journal of Education & Learning Technologies, 2026)
This article investigates the theoretical and practical aspects of integrating artificial intelligence (AI) technologies and digital platforms into the education system. The study analyzes digital transformation processes in the education system of the Republic of Uzbekistan, international best practices, and the impact of AI-based adaptive learning systems on educational quality. A mixed-methods research design was employed, incorporating a questionnaire survey (n=450), a quasi-experimental study (n=120), and statistical analysis. The findings demonstrate that AI-based adaptive learning systems improved student achievement by 25.4 points (47.8%), with a statistically significant difference between experimental and control groups (t=10.15, p
Keywords: Artificial intelligence, digital platform, education system, adaptive learning, digital transformation, educational technology, online education, Uzbekistan.